Digital Frontiers: Meeting Uncertainty (A Review Study) - Slavík, Benjamin (Iluminace, 2021)
The aim of the presented study is to describe the relationship between the thinking of the contemporary visual theorist Daniel Strutt and the French post-structuralist philosopher Gilles Deleuze; the tension between thought and image is mainly analyzed in this study. In his book The Digital Image and Reality: Affect, Metaphysics and Post-Cinema, Daniel Strutt introduced the concept of the digital frontier (his own digital image ontology), which is strongly influenced by Deleuze's thinking (on the one hand by the ontological one in the work Difference and Repetition, on the other hand by the one devoted to the image of modern cinema in the book Cinema 2: The Time-Image). What unites the two authors is the effort to identify the forces that can be a source of human thought activity. They both find these forces in a moment in which man cannot rely on the ontological certainty of the image - and on the contrary, he is forced to create himself in the sphere of uncertainty. The presented study attempts to present this uncertainty in the context of the thinking of both authors.
Keywords: representation; Gilles Deleuze; Daniel Strutt; digital image; analog image